The Old (Woman of the) History: childhood and dictatorchip on the Tightrope (Lygia Bojunga, 1979) (Tempo e Argumento, 2022)
In this article, we seek to reflect on the relationships of experience and domination in the book Tightrope by Lygia Bojunga, published in 1979. With a plot that follows the contradictions of the slow forging process of childhood and sensibilities, the author highlights important dimensions of the political struggle in Rio's class society, highlighting limits and obstacles demarcated by subtle social counterpowers. The circus, world of possibilities, appears in this novel as a space for novelties, in contrast to the dominant repetitions of the world of the powerful, especially threatening for those who tell stories in those years of civil-military dictatorship (1964-1985). The future is an articulating element of hopes in this literature: the evils suffered by the Old Woman of the History are redeemed by the courageous bet that the girl Maria makes in her own memories.
Keywords: literature; Lygia Bojunga; tightrope; childhood; 1964 civil-military dictatorship